Plant Extracts Rich in Polyphenols as Potent Modulators in the Growth of Probiotic and Pathogenic Intestinal Microorganisms - Milutinović, Milica; Dimitrijević-Branković, Suzana; Rajilić-Stojanović, Mirjana (Frontiers in Nutrition, 2021)
Medicinal plants and their extracts contain substantial quantities of polyphenols. As metabolically active plant metabolites, polyphenols are food components with a wide range of biological activities. Given their poor absorbability in the digestive tract their activity towards the human host is typically mediated through interaction with intestinal microbes. As a result, polyphenols comprise a novel group of prebiotics. In this study, we tested the effect of five polyphenol-rich extracts from four medicinal herbs on the growth of probiotic and pathogenic microbes. The studied medicinal herbs were Gentiana asclepiadea L. (willow gentian), Hypericum perforatum L. (St. John's wort), Satureja montana L. (winter savory), and Achillea millefolium L. (yarrow). All these plants are traditionally used for the treatment of digestive problems. Extracts were prepared using safe solvent combinations. We tested the impact of addition of plant extracts on the growth of three probiotic lactobacilli and probiotic yeast Saccharomyces boulardii. The effect of addition of plant extracts to liquid media (concentration range 0.25–10 mg/mL) on the growth of probiotics, was tested in vitro. The antimicrobial activity of the extracts was tested against several opportunistic bacteria and yeast. St. John’s wort, winter savory, and willow gentian extracts showed a stimulative effect on probiotic yeast growth, while the highest growth-stimulating effect was achieved when microwave-assisted yarrow extract was used in the concentration of 0.5 mg/mL. Under these conditions growth of S. boulardii was increased 130-fold. In addition, the yarrow extract stimulated the growth of Lactiplantibacillus plantarum 299v. The growth of two Lacticasibacillus rhamnosus strains was not stimulated by the addition of any extracts. Our results show that plant polyphenol-rich extracts can influence the growth of microorganisms that are typical members of the intestinal microbiota. For the first time we demonstrate that probiotic yeast growth can be stimulated by extracts of medicinal herbs, which when accompanied by suppression of Candida yeasts suggests a potential benefit of the treatment in diseases that are associated with fungal dysbiosis.